PENGEMBANGAN E-LEARNING SCHOOLOGY PADA MASA PANDEMI COVID-19 DI PGSD FKIP UNIVERSITAS SARJANAWIYATA TAMANSISWA - Heri Maria Zulfiati; Elyas Djufri; Trio Ardhian (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2021)
Schoology e-learning is a learning process by utilizing technology because online e-learning media uses computer networks to provide information and communication that if the lecturers use e-learning, there can be changes in learning activities between students and lecturers. This study aims to develop and describe the attractiveness, convenience and usefulness and effectiveness of e-learning which is used as an enrichment in terms of student activity and learning outcomes. It is a research & development research referring to development models that are Analyze, Design, Develop, Implement, Evaluation (ADDIE). Schoology-based e-learning has similar features to Facebook and Schoology also combines social networking and LMS (Learning Management System). The development of schoology-based e-learning can easily obtain information on the learning materials provided by the lecturer even though the lecturer is unable to attend class because through schoology the lecturer can check student attendance, and between lecturers and students can interact socially and also learn together.